Reporting for China : how Chinese correspondents work with the world - Nyiri, Pal (Seattle : University of Washington Press, 2017)
While Western media are shrinking their foreign correspondent networks, Chinese media, for the first time in history, are rapidly expanding worldwide. The Chinese government is financing most of this growth, hoping to strengthen its influence and improve its public image. But do these reporters willingly serve formulated agendas or do they follow their own interests? And are they changing Chinese citizens views of the world? Based on interviews and informal conversations with over seventy current and former correspondents, "Reporting for China" documents a diverse group of professionals who hold political views from nationalist to liberal, but are constrained in their ability to report on the world by Chinas media control, audience tastes, and the declining market for traditional media
Introduction. China and the world -- The worldwide expansion of China's media -- How stories are made: correspondents, editors, and "leaders" -- How correspondents work -- Finding the "China peg" -- Epilogue. Cosmopolitan professionals in the service of the nation
Includes bibliographical references and index.
Keywords: Journalism -- China; Foreign correspondents -- China; Foreign news -- China; Press and politics -- China